L'effectivité des décisions de justice en droit international privé - Groffier, Ethel (Les Cahiers de droit, 1985)
After describing the evolution of the Quebec private international law rules concerning the execution of foreign judgments (Section I), this paper outlines the current procedures of recognition (Section II). Section III explains the statutory provisions designed to facilitate recognition and execution of foreign judgments or to prevent it. In particular, the paper focusses on recent efforts in Quebec towards international cooperation.